A new genus and two new species of monstrilloid copepods (Copepoda: Monstrillidae): integrating morphological, molecular phylogenetic, and ecological evidence. Issue 1 (1st January 2018) - Jeon, Donggu; Lee, Wonchoel; Soh, Ho Young
Abstract: Caromiobenella gen. nov., represented by males of two new species of monstrilloid copepods (Copepoda: Monstrillidae), Caromiobenella castorea sp. nov. (type species) and C. polluxea sp. nov., is established based on morphological, molecular, and ecological evidence. The genus is characterized by the following new combination of morphological characters: 1) relatively short cephalothorax, 2) inconspicuous oral papilla located anteriorly, 3) last antennular segment modified into serrate ridges on the inner distal margin with a general absence of branched setae, 4) modified spinous element 2d2 (elongated, biplumose or both), and 5) two pairs of prominent, crater-like, concave depressions on the anterior dorsum of the cephalothorax. These characters are also shared by several other nominal species hitherto assigned to Monstrilla Dana, 1849 . Molecular analyses of mitochondrial cytochrome c oxidase subunit I (mtCOI) genes and nuclear 28S ribosomal RNA (28S rRNA) genes indicate both that these species are distinct from each other and that, as a group, they are isolated from other known monstrilloid genera. Furthermore, previous studies have shown that one of these species differs from other species of Monstrilla in utilizing a different group of invertebrate hosts, namely gastropods. Based on this integrated data, the new genus comprises six additional species: C. helgolandica (Claus, 1863 ) comb. nov., C. serricornis (Sars, 1921 ) comb. nov., C. arctica (Davis & Green, 1974 ) comb. nov., C. hamatapex (Grygier & Ohtsuka, 1995 ) comb. nov., C. pygmaea (Suárez-Morales, 2000 ) comb. nov., and C . patagonica (Suárez-Morales, Ramírez & Derisio, 2008 ) comb. nov.